Rancang Bangun Media Pembelajaran pada Mata Pelajaran Sistem Pemograman Berbasis IoT Kelas XI di SMK Negeri 1 Pariaman Berbasis Android Menggunakan Smart App Creator - Rizka Amanda; Yasdinul Huda; Vera Irma Delianti; Rido Putra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to develop an interactive learning media based on android using a valid and practical smart app creator to improve students' understanding of the SPBI course in the Industrial Automation Engineering Department of SMK Negeri 1 Pariaman. This study uses the Research and Development (R&D) method with the ADDIE model as a guideline in the development process. The results of this study provide evidence that the interactive learning media created falls into the